Materiality of Non-financial Information: An Examination of the Impact of Directive 2014/95/EU - Ewa RÓŻAŃSKA; Łukasz MATUSZAK (Communications of International Proceedings, 2020)
Purpose: This study aims to investigate whether making non-financial disclosures (NFD) obligatory affect their materiality by focusing on the differences in the materiality of NFD across companies listed on the Warsaw Stock Exchange over the period surrounding the implementation of the Directive 2014/95/EU (hereafter the Directive). Design/methodology/approach: To this purpose, we constructed a novel, hand‐collected materiality index of NFD in line with the reporting requirements introduced by Directive. The sample comprised 71 selected listed companies over 6 years. Findings: The materiality of NFD have increased over the years of analysis. The implementation of the Directive positively influenced the materiality of non-financial information. Originality: Our study contributes to the understanding of the impact of Directive on the materiality of NFD. It has important implications for policy makers because it revealed that mandatory regulations form a crucial instrument in improving the materiality of NFD. Our research suggests that, due to Directive, stakeholders should be provided with more material non-financial information.
Keywords: Materiality principle; relevance; quality of non-financial disclosure; non-financial reporting; Directive 2014/95/EU; ESG disclosure; sustainability disclosure